Evaluations of holey graphene oxide modified ultrafiltration membrane and the performance for water purification. (December 2021) - Ding, An; Ren, Zixiao; Zhang, Yuehua; Ma, Jun; Bai, Langming; Wang, Bo; Cheng, Xiaoxiang
Abstract: Membrane technology has been widely used in the fields of drinking water treatment with the advantages of pollutants separation. However, membrane fouling has become main obstacle in further application. Graphene oxide (GO) and its functionalized derivatives are considered to be ideal membrane modification materials of membrane fouling control. However, GO coated membranes were suffered from serious flux decline which raises challenges for GO modification. In this study, porous holey graphene oxide (HGO) was synthesized by hydrothermal etched GO to modify UF membranes. Water permeability of HGO membrane was more than twice that of GO membrane at the loading of 0.08 g/m 2 . At the optimal loading of 0.08 g/m 2, the rejection rate of HGO coated membrane on natural organic matter (NOM) such as bovine serum albumin (BSA), sodium alginate (SA) and humic acid (HA) was increased from 55%, 29%, 58%–85%, 72%, 92%, and the contact angle was reduced from 71° to 35° with the HGO coating amount of 0.04 g/m 2 . Finally, the membrane fouling resistance distribution of each HGO membrane was analyzed given HA as model pollutant, and the effects of HGO on mitigating the organic fouling of Polyethersulfone (PES) membranes were discussed. The total fouling resistance decreased from 3.45 to 1.73 with HGO coating, the irreversible fouling decreased by 62.86%–95.83%. Standard blocking was dominated during filtration. It was also found that increasing the loading of HGO could delay the conversion of pore blocking to the cake layer. Overall, HGO coating has an application prospect for membrane fouling control. Graphical abstract: Image 1 Highlights: Holey graphene oxide was proposed for UF membrane modification and fouling control. Membrane fouling caused by natural organic matters was significantly mitigated with this strategy. The mechanism of membrane fouling mitigation was studied in details. The proposed strategy has an application prospect in natural water treatment.